Worsening asthma at school is associated with poor psychosocial well-being - Eerika Finell; Asko Tolvanen; Caroline Stridsman; Helena Backman; Linnéa Hedman (European Clinical Respiratory Journal)
Objective To study whether worsening asthma at school was related to generic health-related quality of life (HRQoL) and asthma-related impact and worry among 15-year-olds with current asthma in Sweden. In addition, we studied the association between worsening asthma at school at age 15 and the change in the degree to which asthma interfered with daily activities between ages 15 and 19 years.Methods Within the Obstructive Lung Disease in Northern Sweden (OLIN) studies, a cohort of schoolchildren has been followed from age 8 years until 19 years of age. In the current study, the sample included 266 adolescents with physician-diagnosed asthma, and either wheeze or use of asthma medication during the last 12 months at age 15 years.Results At age 15, HRQoL scores were lower among those who reported worsening asthma at school (standardised beta (β) =  −0.18, p = 0.003), they had more asthma-related worries (β =  −0.33, p < 0.001) and asthma impacted their life during activities more (β =  −0.46, p < 0.001) than those whose asthma did not worsen. Furthermore, the more adolescents reported that asthma worsened at school at age 15, the more it was associated with the increase in the degree to which asthma interfered with their activities between 15 and 19 years (β = 0.14, p = 0.038).Conclusions Worsening asthma at school was associated with lower generic health-related quality of life, higher asthma-related worry and impact on daily activities among teenagers with asthma.